Sold out or bought in? Complexities of the X Swatch as subcultural accessory for the straight edge scene. Issue 1 (1st March 2022) - Sklar, Monica; Strübel, Jessica; Haenfler, Ross
This research explores lifestyle consumerism and inquires into a subcultural community's use of a mainstream fashion object to express alternative values. The 'X-rated Swatch Watch' is extremely popular within straight edge, a clean-living punk offshoot in which participants abstain from alcohol, tobacco and illicit drugs. Swatch first released the watch in 1987 with a black band and white face featuring a large black 'X', a prominent symbol in the straight edge scene visible on clothing, in tattoos and drawn on hands. The limited-edition watch became highly collectable on the second-hand market and was re-released by Swatch in 2018 with design changes, including larger size and more colour options. The first and second incarnations of the watch, as well as knockoffs, indicate aesthetic trends in the fashion cycle, evolutions as well as stagnations in subcultural individual and community expression, and the complexities of a mass market item that has multiple cultural meanings within the same time period. In this article, we use qualitative mixed methods to explore the significance of the watch for United States straight edgers who own or express interest in the watch. Primary data collection included surveys, social media discussions, participant observation and archive visits. Results indicate that wearers utilize this watch to strengthen their straight edge identity and communal connections to similar individuals and to the historic lineage of their lifestyle. X Swatch consumers are not overly concerned with the duality of subcultural and mainstream meanings as they compartmentalize their community from wider society.